2016
DOI: 10.1007/978-3-319-33111-9_14
|View full text |Cite
|
Sign up to set email alerts
|

Potential Improvement of Building Information Modeling (BIM) Implementation in Malaysian Construction Projects

Abstract: Part 4: Building Information Modeling (BIM)International audienceApplication of building information modeling (BIM), such as preview design clashes and visualize project’s model increase effectiveness in managing construction projects. However, its implementation in Malaysian construction projects is slow in order to see and gain the benefits. Therefore, this paper aims to explore on potential improvement that could increase BIM implementation in construction projects. A literature review was conducted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Another management challenge is the question that arose among the stakeholders, which is who shall be responsible for developing the models and how the costs will be distributed. Hence, to clear this issue, solutions have to be created by researchers, vendors and professional organizations together so that the use of BIM will increase in the Malaysian construction industry (Latiffi, Mohd, & Rakiman, 2015c). Hong, et al (2016) reported that it is hard to adopt new information technology (IT) in the industry due to technical reasons.…”
Section: Managementmentioning
confidence: 99%
“…Another management challenge is the question that arose among the stakeholders, which is who shall be responsible for developing the models and how the costs will be distributed. Hence, to clear this issue, solutions have to be created by researchers, vendors and professional organizations together so that the use of BIM will increase in the Malaysian construction industry (Latiffi, Mohd, & Rakiman, 2015c). Hong, et al (2016) reported that it is hard to adopt new information technology (IT) in the industry due to technical reasons.…”
Section: Managementmentioning
confidence: 99%
“…Order of subjects is according to authors' opinions on the importance of subjects and different from the frequency of appearances on the articles. [10], [11], [12], [13], [14], [7], [15], [16], [17], [18], [19], [20], [21] Cultural [22], [23], [2], [24], [10], [11], [12], [13], [25], [8], [16], [26], [17], [27], [28], [29], [ 30] Management [31], [1], [32], [12], [33], [15], [34], [35], [36], [17], [37], [38], [39], [40], [41] Financial [22], [11], [12], [13],…”
Section: Bim Implementation Challengesmentioning
confidence: 99%
“…BIM is defined as the method of generation execution and monitoring of the "building data" during its life process. Moreover, BIM is also known as a combination of process and technology to improve efficiency and effectiveness of delivering a project from inception to operation and maintenance [10]. In construction projects, BIM has been used by architecture, engineering and construction or facilities management (AEC/FM) to implement collaborative management of construction projects between all stakeholders.…”
Section: Plm-bim Definitions and Objectivesmentioning
confidence: 99%
“…It creates and manages huge landscape of opportunities by associating with like-minded and in-lined areas and processes. In [10], they state that BIM is a process that brings all data or information on project design together in one parametric model giving benefits to construction projects in terms of time, cost and quality and helps design team to solve the design clashes early in pre-construction stage. As a summary, BIM consists of at least three dimensions: process, technology and people.…”
Section: Plm-bim Definitions and Objectivesmentioning
confidence: 99%